2009
DOI: 10.1088/0957-4484/20/44/445602
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for the functionalization of γ-irradiated single wall carbon nanotubes with DNA

Abstract: In this work we describe a novel method for highly efficient functionalization of single wall carbon nanotubes (SWCNTs) by DNA wrapping. Exposure of SWCNTs to gamma-irradiation (50 kGy) has lowered by one order of magnitude the amount of single stranded deoxyribonucleic acid (ssDNA) required for SWCNT modification. The resulting hybrids of gamma-irradiated SWCNTs and ssDNA were characterized by optical absorbance spectroscopy, Raman spectroscopy and Fourier transform infrared spectroscopy. Atomic force microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…A stable water suspension of graphene nanoparticles was prepared by aqueousphase exfoliation of graphite in the presence of non-ionic/non-toxic macromolecule polyvinylpyrrolidone (PVP) [19], while single-wall CNT were made water-soluble by functionalization with DNA or anionic detergent sodium dodecylbenzenesulfonate (SDBS), as previously described [20,21]. Briefly, 500 mg of crystalline graphite powder (synthetic, 6 mm; Timcal, Bodio, Switzerland) were suspended in 100 ml of deionized water containing 1 g PVP (SigmaeAldrich, St. Louis, MO), while 50 mg of single-wall CNT (95%; BuckyUSA, Houston, TX) were added to 100 ml of deionized water containing 1 mg of heat-denatured single-stranded DNA or 2 mg SDBS (both from SigmaeAldrich, St. Louis, MO).…”
Section: Preparation and Characterization Of Graphene Nanoparticles Amentioning
confidence: 99%
“…A stable water suspension of graphene nanoparticles was prepared by aqueousphase exfoliation of graphite in the presence of non-ionic/non-toxic macromolecule polyvinylpyrrolidone (PVP) [19], while single-wall CNT were made water-soluble by functionalization with DNA or anionic detergent sodium dodecylbenzenesulfonate (SDBS), as previously described [20,21]. Briefly, 500 mg of crystalline graphite powder (synthetic, 6 mm; Timcal, Bodio, Switzerland) were suspended in 100 ml of deionized water containing 1 g PVP (SigmaeAldrich, St. Louis, MO), while 50 mg of single-wall CNT (95%; BuckyUSA, Houston, TX) were added to 100 ml of deionized water containing 1 mg of heat-denatured single-stranded DNA or 2 mg SDBS (both from SigmaeAldrich, St. Louis, MO).…”
Section: Preparation and Characterization Of Graphene Nanoparticles Amentioning
confidence: 99%
“…In Fig. 6(b)-(d) one can observe bands at about 2837 and 2920 cm −1 , which correspond to C H bonds in the nanotube matrix [29]. Moreover, intensity of the C H bonds increases with increasing the irradiation fluence.…”
Section: Ftir Analysismentioning
confidence: 85%
“…All samples were irradiated with the dose of 50 kGy. In the curves 1, 2, 3 and 4 one can observe bands at around 2830 and 2900 cm −1 , which correspond to C\H bonds in the nanotube matrix [29]. The spectra of γ-air-SWCNTs (curve 2), γ-ammonia-SWCNTs (curve 3) and γ-water-SWCNTs (curve 4) exhibit broad band at 1550, which stem from C\O stretching vibration of COOH functional groups.…”
Section: Ftir Spectroscopymentioning
confidence: 92%
“…Authors confirmed that the changes in electrical conductivity and Young modulus correlate with the dose of gamma irradiation. Applying a relatively low dose of gamma irradiation on SWCNTs, it was observed that gamma irradiated nanotubes were more soluble in water compared to pristine ones [29].…”
Section: Introductionmentioning
confidence: 99%